2013
DOI: 10.14260/jemds/1023
|View full text |Cite
|
Sign up to set email alerts
|

Male Participation in MCH Services

Abstract: ABSTRACT:Research question: How many male partners are aware and involved in maternity care of their partners and in child health? Aims and Objective: To study the level of awareness and involvement of male partners in maternity care and child health setting: Head-quarter village of an adopted primary health centre of Bharati Vidyapeeth university Medical College and Hospital, Sangli. DESIGN: Cross sectional study. Material and Method: male partners of women who delivered in last two years of study period, int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…This study was conducted in the rural setup and it was found that the proportion of joint or extended families was more as compared to nuclear families. Similar finding was seen in the study of Jogdand et al ., 2013,[ 9 ] which was also conducted in a rural area in which 62.9% of the study subjects belonged to joint or extended families and 37.1% belonged to nuclear families.…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted in the rural setup and it was found that the proportion of joint or extended families was more as compared to nuclear families. Similar finding was seen in the study of Jogdand et al ., 2013,[ 9 ] which was also conducted in a rural area in which 62.9% of the study subjects belonged to joint or extended families and 37.1% belonged to nuclear families.…”
Section: Discussionmentioning
confidence: 99%